POLA PEMODELAN DINAMIS ANTARA BIOMASSA UDANG, JUMLAH PAKAN, DAN BAHAN ORGANIK PADA EKOSISTEM TAMBAK - Abdul Wafi; Heri Ariadi (EnviroScienteae, 2022)
Shrimp growth patterns will dynamically affect feeding patterns and organic waste conversion in the pond ecosystems. The purpose of this study was to determine the dynamic correlation between the amount of shrimp biomass, feed, and the solubility of organic matter in the shrimp pond ecosystem at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo, Situbondo Regency. The research method used is an ex-pose facto causal design with time series field data collection. The data taken are water quality parameter, pond water organic matter parameters, feeding data, shrimp sampling data. The results showed that the water quality parameters in aquaculture ponds were still quite good, namely pond A1 pH value 8.2, temperature 29.20C, dissolved oxygen 5.58 mg/L, salinity 25 ppt, and brightness 37 cm. For pond A2, the pH value is 8.1, the temperature is 29.20C, the dissolved oxygen is 5.52 mg/L, the salinity is 25 ppt, and the brightness is 34 cm. From the results of dynamic modeling analysis, it is found that there is a close correlation between the feeding process and the amount of waste generated in the pond with a ratio of 1: 2.86. then the process of shrimp growth rate is correlatively strongly influenced by the factor of feeding which is carried out in an aggregated manner. Based on the results of this study, it can be concluded that according to the interpretation of the results of the analysis of the dynamic modeling system, there is a positive correlation between the increase in the amount of shrimp biomass with the quantity of feed and the abundance of organic matter in the pond which is estimated to take place in an aggregate manner.